Pectin-hydroxypropylmethylcellulose drug delivery system for colon targeting - Design and in vitro evaluation - (:unkn) unknown (ECV-EDITIO CANTOR VERLAG MEDIZIN NATURWISSENSCHAFTEN, 1999)
Pectin-Hydroxypropylmethylcellulose (HPMC) matrix tablets were prepared and evaluated of their dissolution/erosion properties to assess their colon targeting:possibility based on a gastrointestinal transit time concept. Dosage forms were tested in water and also separately in 0.1 N HCl and pH 6.8 buffer systems. HPMCs of three different molecular weights were incorporated as 25% into a pectin USP matrix in addition to pure pectin tablets. The effect of a pectin-degrading enzyme (Pectinex 3XL) on dissolution rate was also studied. It was found that dissolution/erosion rates were faster in water than in buffer solutions. The t(50) Values were 3, 3.4, 5.0, and 6.0 h in water and 4.6, 5.3, 9.7, and 11.7 h in a buffer system dependent on the viscosity grade of HPMC. Addition of 25% HPMC improved the mechanical properties of pectin matrix. Pectinex 3XL accelerated the degradation of pectin tablets as well as HPMC content of matrix. Pectin-HPMC system is recommended as protective wall layers to protect and carry protein drugs to the colon for targeting.
Keywords: colon targeting; drug targeting; hydroxypropylmethylcellulose; pectin; pectinase; tablets, dissolution, erosion; CALCIUM PECTINATE; FORMULATIONS